Leveling up in corporate training: Unveiling the power of gamification to enhance knowledge retention, knowledge sharing, and job performance - Alexandru Capatina; David Juarez-Varon; Adrian Micu; Angela Eliza Micu (Journal of Innovation & Knowledge (JIK), 2024)
This paper extends the fast-growing research stream on gamification in corporate training by examining the impact of gamification on employees' knowledge retention, knowledge sharing, and job performance. A mixed-methods approach was employed. Quantitative data from surveys and qualitative insights from experimental research were combined to ascertain the effectiveness of gamification techniques in corporate training. The sample consisted of 110 employees and business owners who attended gamified training sessions powered by the Discovery-Innovation-Growth platform. Participants were aged 18 to 64 years and had diverse educational backgrounds and job positions. They were also based in different European countries (Spain, France, Germany, United Kingdom, Italy, Finland, and Romania). The sample characteristics thus ensured comprehensive coverage of different employee profiles. Gamification significantly enhanced knowledge retention and job performance. Gamification techniques such as points, badges, and leaderboards positively influenced employee engagement, which in turn boosted the ability to retain and apply knowledge effectively at work. Social interaction mediated the relationship between gamification techniques and knowledge sharing, highlighting the role of collaborative learning environments. These insights offer valuable guidance for corporate instructors and human resource (HR) professionals aiming to develop engaging and personalized training programs that meet diverse employee needs and learning preferences. This study contributes to the theoretical framework of gamification in adult learning and organizational development, paving the way for future research in this dynamic field.
Keywords: M53; D83; 650; Gamification; Training; Knowledge dynamics; Job performance; Eye tracking